Inner talk ([S.l.] : Progreesive Awareness Research, 2002)
This programs are mind training tools which uses geometry and color to deepen interpersonal states of awareness and relaxation. They are designed to assist in slowing down brain wave activity and producing altered states of consciousness.
vol. 1. Golf like a pro (29 min.) - vol. 2. Creative genius (30 min.) - vol. 3. Accelerated learning and memory (27 min.)
Title from cd cover.
DVD format.
Keywords: Self-help techniques; Self-talk.; Self-actualization (Psychology).